Changes in mesospheric dynamics at 78°N, 16°E and 70°N, 19°E: 2001–2012. Issue 7 (2nd April 2013) - Hall, C. M.; Tsutsumi, M.
Abstract: [1] Mesospheric wind data from meteor wind radars situated on Svalbard (78°N, 16°E) and the Norwegian mainland (70°N, 19°E) are examined for evidence of systematic change during the interval 2001–2012. For both locations, we find changes that suggest a strengthening of the summer westward jet, a weakening of the local winter eastward flow and, yet at the same time, weak evidence for any significant corresponding trend in the winter poleward flow. There is also a suggestion of an increase in the altitude of the summer polar jet, but more data will be required to confirm this. The main finding of a strengthening zonal flow is consistent with earlier studies and also with a contemporary scenario of progressive strengthening of the Brewer‐Dobson circulation. We show that inclusion of sudden stratospheric warmings strongly influences trends. There is no obvious causality between the changes detected over the 2001–2012 time interval and the solar cycle parameterized by total solar irradiance. Key Points: Significant changes in middle atmosphere dynamics over the last decade Quantitative approach to confidences in derived trends Novel pilot study showing mesospheric jet strengthening and increasing in height